2021
DOI: 10.1101/2021.05.14.21257233
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Longitudinal changes in home-based arts engagement during and following the first national lockdown due to the COVID-19 pandemic in the United Kingdom

Abstract: Aims: This study aimed to examine potential heterogeneity in longitudinal changes in home-based arts engagement during the first national lockdown and following gradual easing of restrictions in the UK. Further, it sought to explore factors that were associated with patterns of longitudinal changes in home-based arts engagement. Methods: Data were from the UCL COVID-19 Social Study. The analytical sample consisted of 29,147 adults in the UK who were followed up for 22 weeks from 21st March to 21st August 2020… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 20 publications
(35 reference statements)
1
7
0
Order By: Relevance
“…Our stepdown analysis highlighted that online cultural engagement might especially be an avenue to regulating mood, which possibly drives other positive impacts (stateanxiety, subjective wellbeing). This highlight of mood regulation is supported by past research, which has found emotion and mood regulation as a common beneficial outcome of a variety of types of arts and cultural engagement (Fancourt et al, 2019(Fancourt et al, , 2021Ivcevic & Brackett, 2015).…”
Section: Potential Mechanisms For the Modulation Of Mood Anxiety And Wellbeingsupporting
confidence: 61%
See 3 more Smart Citations
“…Our stepdown analysis highlighted that online cultural engagement might especially be an avenue to regulating mood, which possibly drives other positive impacts (stateanxiety, subjective wellbeing). This highlight of mood regulation is supported by past research, which has found emotion and mood regulation as a common beneficial outcome of a variety of types of arts and cultural engagement (Fancourt et al, 2019(Fancourt et al, , 2021Ivcevic & Brackett, 2015).…”
Section: Potential Mechanisms For the Modulation Of Mood Anxiety And Wellbeingsupporting
confidence: 61%
“…However, an ongoing mental health survey conducted by University College London in the UK (Covid-19 Social Study, 2020) found, more than a fifth of 70,000 respondents engaged more with the arts during lockdown than before. Those individuals who identified as having a mental illness or disability were likely to engage more in the first 22 weeks, which was speculated to be due to the move of cultural institutions online (Bu et al, 2021), however this study did not quantify whether such use translated to actual effects.…”
Section: Digital Online Art-would This Translate To Similar Wellbeing Impacts? (Rq1)mentioning
confidence: 93%
See 2 more Smart Citations
“…These changes fluctuated in line with the easing and tightening of social distancing throughout the pandemic, with many cultural venues oscillating between inperson and digital offerings, alongside hybrid models. The impact of these ongoing changes provided many challenges for the sector including fewer employment opportunities (Office for National Statistics, 2021), but also some opportunities including increased digital production (Radermecker, 2020), and some increases in home-based arts engagement (Bu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%